Evaluation of Different Growing Media for Tomato and Sweet Pepper Seedlings Raising in Pokhara, Nepal - Lohani, Santosh; Adhikari, Saroj; Aryal, Lok Nath; Bhusal, Yubraj; Kadariya, Manahar; Aryal, Sunil (Journal of Agriculture and Environment, 2023)
Nine different compositions of growing media were evaluated for growing tomato and capsicum in two consecutive years (2020 and 2021). Experiments were conducted in Randomized Complete Block Design (RCBD) under rain shelter (poly house) with three replications. The growing media were Cocopeat, FYM+Cocopit+Perlite, FYM+ Cocopit+Vermiculite, FYM+Perlite, FYM+Soil, FYM+Vermiculite, Vermicompost+Perlite, Vermicompost +Soil and Vermicompost+Vermiculite. There were significant (P<0.05) differences in the observed parameters like number of seedlings emergence, number of seedling establishment, number of leaves, seedling height and diameter of seedling stem among the tested growing media. The highest seedling emergence of tomato and sweet pepper were recorded in cocopeat as a growing media. After 30 days after seed sowing (DAS) in tomato, the highest number of seedling (103.5) were found in Cocopeat and the tallest seedling height (19.92 cm) was found in Vermicompost+ perlite. Similarly, in Capsicum (40DAS), the highest number of seedling (83.5) were found for the growing media Cocopeat only, followed by Vermicompost + Perlite (78) and the tallest seedling height (13.89 cm) was found in Vermicompost+Vermiculite grown seedlings. The good root plug formation was found for the use of cocopeat. Therefore, use of vermicompost or FYM in the mixed form with cocopeat or the soil as a growing media would be sustainable technology for commercial seedling production of vegetables.